Characterization of volatile thiols in Chinese liquor (Baijiu) by ultraperformance liquid chromatography–mass spectrometry and ultraperformance liquid chromatography–quadrupole-time-of-flight mass spectrometry - Yan, Yan; Lu, Jun; Nie, Yao; Li, Changwen; Chen, Shuang; Xu, Yan (Frontiers in Nutrition, 2022)
Volatile thiols give a unique flavor to foods and they have been extensively studied due to their effects on sensory properties. The analytical assay of volatile thiols in food is hindered by the complexity of the matrix, and by both their high reactivity and their typically low concentrations. A new ultraperformance liquid chromatography (UPLC) strategy has been developed for the identification and quantification of volatile thiols in Chinese liquor (Baijiu). 4,4’-Dithiodipyridine reacted rapidly with eight known thiols to form derivatives, which provided a diagnostic fragment ion (m/z 143.5) for tandem mass spectrometry (MS/MS). To screen for new thiols, Baijiu samples were analyzed by means of UPLC−MS/MS screening for compounds exhibiting the diagnostic fragment ion (m/z X→143.5). New peaks with precursor ions of m/z 244, 200 and 214 were detected. Using UPLC with quadrupole-time-of-flight mass spectrometry (UPLC–Q-TOF–MS) and authentic standards, ethyl 2-mercaptoacetate, 1-butanethiol and 1-pentanethiol were identified in Baijiu for the first time. Commercial Baijiu samples were analyzed with the new method and the distribution of 11 thiols was revealed in different Baijiu aroma-types. The aroma contribution of these thiols was evaluated by their odor activity values (OAVs), with the result that 7 of 11 volatile thiols had OAVs > 1. In particular, methanethiol, 2-furfurylthiol, and 2-methyl-3-furanthiol had relatively high OAVs, indicating that they contribute significantly to the aroma profile of Baijiu.